The Effect of Active VitaminD on Treatment of Proteinuria in Patients with Diabetic Nephropathy without Vitamin D Deficiency - Nader Saeedi; Mohammadreza Rezvanfar; Mehdi Hadidi; Farvah Asgharizadeh Mahani; Mojtaba Ahmadlou (Majallah-i dānishgāh-i ̒ulūm-i pizishkī-i Arāk, 2016)
Abstract Background: The renin-angiotensin system(RAS) has a major role in development of diabetic nephropathy and blocking of RAS by inhibitors and blocking of angiotesin receptors is standard treatment for preventing kidney disease and proteinuria. It is reported that VIT-D analogues are able to suppress renin exertion and improve proteinuria. The aim of this study is to evaluate the effect of VitD analogue (calitriol) on reducing proteinuria in patients with diabetic nephropathy. Materials and Methods: In this clinical trial study, 132 eligible patients that had diabetic nephropathy and hadn’t vit D deficiency were selected. The patients were divided into two equal groups. First group received the combination of losartan 25mg twice daily and calcitriol 0.25mg and second group received losartan 25 mg twice daly alone for 3 months. The FBS, lipid profile, ESR-CRP BUN, Cr, HbA1c, Ca, P, and 24 hours urine protein were evaluated in all patients at beginning and end of study and the results were statistcally compared. Results: The 24-hour urine protein in losartan and calitriol group was improved compared to losartan. This difference was statistically significant (p=0.003). As well as, in kidney function (BUN, Cr) in the losartan and calcitriol group compared to losartan alone was significantly improved(p<0.05). Conclusion: Combination of calcitriol with angiotesin receptor blockers(ARBs) is more effective than ARBs alone in improvement of proteinuria and real function.